The science of consciousness – Basics, models, and visions. Issue 4 (December 2015) - Hinterberger, Thilo
Highlights: Functions related to conscious perceptions are reflected in the event-related potentials of the EEG. The mental observer might be regarded as an internal reference observing an internal mental representation. Observation is a reduced but meaningful excerpt of the mental representation. The basic values of humanity can be derived from the properties of subjective experience or observation. Consequently, a science of consciousness has to consider the impact of subjective qualities on health. Abstract: This article presents a few models and aspects of the phenomenon consciousness that are emerging from modern neuroscience and might serve as a basis for scientific discourse in the field of Applied Consciousness Sciences. A first model describes the dynamics of information processing in the brain. The evoked electric brain potentials represent a hierarchical sequence of functions playing an important role in conscious perception. These range from primary processing, attention, pattern recognition, categorization, associations to judgments, and complex thoughts. Most functions seem to be implemented in the brain's neural network operating as a neurobiological computer. Another model treats conscious perception as a process of internalisation leading to the "self" as conscious observer. As a consequence, every conscious perception can be seen as a reduced and already interpreted observation of an inner representation of an outer or imagined "world." Subjective experience thus offers properties which can only be experienced from the inside and cannot be made objective. Basic values of humanity such as responsibility, love, compassion, freedom, and dignity can be derived from these subjective qualities. Therefore, in contrast to the Natural Sciences, the Science of Consciousness additionally is challenged to deal with those subjective qualities, emphasizing the resulting influence on health, social interactions, and the whole society.